Comparative Analysis of Price and Service Quality Factors on Shopee and Lazada User Loyalty - Restu Salma Maulida; Ruqia Mohamud Haji Mustafa; Maria Elisabet Assem; Siti Hajar (Westscience Press, 2024)
This study aims to determine whether or not there are differences in price and quality factors on Shopee and Lazada user loyalty. The research method used is variable data, namely by giving questionnaires to Shopee and Lazada users with a sample size of 36 respondents. The analysis technique used in this study is the Normality Test, Homogeneity Test, and Independent Sample T-Test. The results of this study indicate that there is no difference between product quality and price on the Shopee and Lazada marketplaces. While in data analysis using SPSS 24. Keywords: Product Quality, Loyalty, Price, Shopee, Lazada.